Primary Renal Carcinoid with Bilateral Multiple Clear Cell Papillary Renal Cell Carcinomas - Daniel A. Anderson; Maria S. Tretiakova (Hindawi Limited, 2017)
Clear cell papillary renal cell carcinoma (CCPRCC) is a newly recognized entity in the 2016 WHO classification and usually presents as a small, circumscribed, solitary mass of indolent nature. CCPRCCs could seldom occur in conjunction with other synchronous or metachronous kidney tumors and even less frequently as bilateral masses. To our knowledge, multiple bilateral CCPRCCs have never been described with the existence of a synchronous well-differentiated neuroendocrine tumor of the kidney and hence reported here as a unique case. This case report highlights the importance in considering this entity and its unusual presentation in the differential diagnosis as a possible mimicker of Von Hippel-Lindau syndrome.